Optimized Local Infarct Restraint Improves Left Ventricular Function and Limits Remodeling - Koomalsingh, Kevin J. (2012)
BACKGROUND: Preventing expansion and dyskinetic movement of a myocardial infarction (MI) can limit left ventricular (LV) remodeling. Using a device designed to produce variable alteration of infarct stiffness and geometry, we sought to understand how these parameters affect LV function and remodeling early after MI. METHODS: Ten pigs had posterolateral infarctions. An unexpanded device was placed in 5 animals at the time of infarction, and 5 animals served as untreated controls. One week after MI animals underwent MRI to assess LV size and regional function. In the treatment group, after initial imaging, the device was expanded with 2ml, 4ml, 6ml, 8ml and 10ml of saline. The optimal degree of inflation was defined as that which maximized stroke volume (SV). The device was left optimally inflated in the treatment animals for three additional weeks. RESULTS: One week after MI, device inflation to ≥6ml significantly (p<0.05) decreased endsystolic volume (ESV) (0ml:59.9ml±3.8, 6ml:54.0ml≥±3.1, 8ml:50.5ml±4.8, 10ml:46.1ml±2.2) and increased ejection fraction (EF) (0ml:34.6%±1.6, 6ml:39.7%±0.9, 8ml:43.1%±2.7, 10ml:44.1%±0.9). SV significantly (p<0.05) improved for the 6ml and 8ml volumes (0ml: 31.2ml±2.6, 6ml: 35.7ml±2.0, 8ml: 37.5ml±1.9) but trended downward for 10ml (36.6ml±2.8). At four-weeks after MI, end-diastolic volume and ESV were unchanged from one-week values in the treatment group while the control group continued to dilate. SV (38.2±4.4ml vs. 34.0.1±4.8ml, p=0.08) and EF (36.0±2.6% vs. 27.6±1.4%, p=0.04) were also better in the treatment animals. CONCLUSIONS: Optimized isolated infarct restraint can limit adverse LV remodeling after MI. The tested device affords the potential for a patient-specific therapy to preserve cardiac function after MI.